Implementasi Edukasi Parenting di Era Digital bagi Masyarakat Indonesia di Luar Negeri - Mirawati Mirawati; Winti Ananthia; Endah Silawati; Yeni Yuniarti (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
Parenting has a very important role in the growth and development of children. This paper examines the application of parenting education for Indonesians abroad. This activity involved 14 participants from the Indonesian School of Davao, Philippines. The method used is Participatory Action Research (PAR), which is carried out in a participatory manner with the aim of encouraging changes in the living conditions of participants for the better. The implementation of parenting education in the digital era uses synchronous modes through video conference platforms and asynchronous through the use of websites. The results of this activity showed a positive response from the participants and shared perceptions regarding the importance of care in families and schools, especially for the development of children's character.